Adaptation of material deposition parameters to account for out-time effects on prepreg tack. (June 2020) - Smith, A.W.; Endruweit, A.; Choong, G.Y.H.; De Focatiis, D.S.A.; Hubert, P.
Abstract: A single-stage peel method was employed to determine the relationship between key processing parameters and tack for a standard aerospace carbon/epoxy prepreg subjected to various levels of room-temperature out-time. The temperature-dependent viscoelasticity of the resin was studied using parallel plate rheometry and modelled using a simple Arrhenius equation. Differential scanning calorimetry and gel permeation chromatography results showed that, over a period of 35 days under ambient conditions, resin T g increased, while no significant change in polymer chain length was observed. Time-temperature superposition was applied to construct tack master curves for each out-time interval, which were shown to approximately coincide when considering shift factors attributed to changes in T g . Process maps considering prepreg out-time were generated using tack master curves to inform process parameters and achieve desirable tack levels. This type of tailored process control is anticipated to improve resource utilization when manufacturing large preforms which take several days to complete.